Appstravaganza. - The Mac Life Staff
Whether you've own your iPhone for a year or a day, you've by now discovered the wonders of the App Store. Even if you limit yourself to freebies, there's an enormous range of choice in Apple's online marketplace for iPhone apps--the App Store is so enormous, in fact, it's quite treacherous to wade into it with no guidance other than a vague idea about "some cool-looking app your buddy had on his iPhone" and the poorly written (and even more egregiously punctuated) user reviews. And so we present our blowout roundup of iPhone app reviews. Let us--the lucky but poorly paid few who make a living overburdening our iPhones with apps "because it's our job"--take you on a tour of the 51 best (and in some cases weirdest or worst) apps in the App store. Because with 25,000 apps and counting, it's easy to choose poorly--or rashly. But you don't ave to, because we've done the legwork for you (and we've got smudgy iPhone screens to prove it). While we're at it, we also offer up crucial iPhone accessories to keep your apps happy, along with some handy how-tos, and other must-know tips and tricks.
Keywords: iPhone (Smartphone); Digital mixology; Apps Store; Lexcycle Stanza